Effect of industrial powder on mechanical properties of glass fiber reinforced epoxy composite - Aseel Basim Abdul-Hussein (Iraqi Journal of Physics, 2019)
In the present study, composites were prepared by Hand lay-up molding and investigated. The composites constituents were epoxy resin as the matrix, 6% volume fractions of Glass Fibers (G.F) as reinforcement and 3%, 6% of industrial powder (Calcium Carbonate CaCO3, Potassium Carbonate K2CO3 and Sodium Carbonate Na2CO3) as filler. Density, water absorption, hardness test, flexural strength, shear stress measurements and tests were conducted to reveal their values for each type of composite material. The results showed that the non – reinforced epoxy have lower properties than composites material. Measured density results had show an incremental increase with volume fraction increase and water absorption, hardness, flexural strength and shear stress results had show an incremental increase with volume fraction increase and with smaller particle size.